Pengaruh Pelatihan dan Motivasi terhadap Kinerja Karyawan PT. Golden Blossom Sumatra - Libani, Ronal; Handayani, Susi; veronica, Meilin (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to analyze the effect of training and motivation on employee performance at PT Golden Blossom Sumatra. The type of data used in this study is by using primary data and secondary data obtained from questionnaires and obtained from companies. The research method used is multiple linear regression analysis. The results indicates that training (X1) and motivation (X2) simultaneously had a significant effect on employee performance (Y), but separately each variable had a negative effect on employee performance (Y). This research is hoped to become additional literature on the topic of job training, work motivation and employee performance